KNOWLEDGE, ATTITUDES, AND PRACTICES OF USING MASKS BY THE COMMUNITY DURING THE COVID-19 PANDEMIC IN INDONESIA - Cipta Pramana, Lia Kurniasari, Budi Santoso, Iis Afrianty, Armia Syahputra, Fajrin Noviyanto, Lukman Handoko, Respati Wulandari, Andi Susilawaty (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Background: The use of mask is one of the methods for preventing the transmission of coronavirus (COVID-19). The provision of intensive knowledge to the community about mask usage is needed, therefore, effectively reducing the spread of the disease. The purpose of this research is to investigate the knowledge, attitudes, and practices of using masks in the prevention of COVID-19 transmission. Methods: This study adopted an online survey using a questionnaire in Google Form, consisting of demographic characteristics, participants’ knowledge about masks, and their wearing practices in limiting COVID-19 transmission. A total of 25 statements were submitted, as respondents answered true or false only. The data were analyzed using a computer statistical tests program (SPSS 21.0). The t test and ANOVA were used in determining the difference in knowledge scores. Results: There were 501 selected participants with the average age of 30 years (SD = 11.25, range = 16-68), and majority were females (359, 71.1%). There were 329 (65.7%), 112 (22.4%), and 60 (12%) respondents using cloth, surgical, and both types of masks, respectively. Most of them have the prior knowledge that masks should be used both indoors and outside home (59.3%), and this has served effectively in the reduction of COVID-19 transmission (99.4%). Conclusion: The good knowledge, attitude, and the proper use of face masks were effective in the prevention of COVID-19 transmission. Moreover, the community under study had fairly good knowledge and appropriate mask usage, therefore, reducing the spread of this disease during the pandemic.